Utilization of AIS Satellite Data as Behavior Information Towards Interruption Violations in the Makassar Strait - Hadinata, Tri; Sutanto, Rudy; Julian, James; Yudho Prakoso, Lukman; Putra, Demo (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2023)
Indonesia is the world’s largest archipelagic country, with a coastline of 81,000 km. Indonesia’s beaches and seas are rich in natural resources, especially marine commodities like fish. The abundance of fish in the Indonesian seas has led to crimes committed by domestic ships not equipped with documents and foreign vessels. This study aims to analyze the causes of crime in the Makassar Strait with a crime orientation in the middle of the sea. In particular, this study also examines the security monitoring process using AIS Satellite. So that in the future, the enforcement carried out by stakeholders related to sea and maritime security will become more conducive and transparent. This research method uses a qualitative descriptive approach to describe data from AIS satellites in the Makassar Strait. The data collection process is carried out by taking satellite data directly and processing it so that some information about ship types and loading and unloading activities can be known comprehensively. Then it is used to determine which ships are initially identified as committing a violation. This information is used to act effectively, efficiently, and appropriately on sea breaches. This method is expected realization that institutions and stakeholders can work together to patrol at sea and promptly act against violations at sea. The discussion location is in the Makassar Strait because the area borders other countries and is one of the locations for abundant fish resources and international shipping lanes. The data for identifying ships suspected of committing crimes in the Makassar Strait was processed from 2019 to 2022. The violations include 22 smuggling ships, 13 drug smuggling ships, and 12 offending crime ships. The data revealed significant violations. Thus, from the analysis results, it is better to need the right timing in implementing patrols and the appropriate momentum for enforcement. Therefore, AIS Satellite is expected to help and improve law enforcement in that location.